Trump's Speech about Jerusalem: An Analysis on Persuasive Strategies - Faiz, Ahmad; Yulianti, Andi Indah; Septiana, Dwiani (State institute of islamic studies salatiga, 2020)
Speaker delivers a speech to achieve the goal indicating the use of persuasive strategies. This research investigates the persuasive strategies used by Donald Trump on his speech about Jerusalem. The aim of this research is to analyze the types of persuasive strategies on Donald Trump’s speech about Jerusalem. Jerusalem is a holy place where many beliefs live together such Islam, Christianity, Jews, etc. Its territory surrounds Palestine and Israel, as both have a great rivalry in an old war. Donald Trump showed his sympathy toward Jerusalem through his speech. In influencing hearers, Trump’s speech reflected persuasive strategies. Persuasive strategies are expressed to influence and change hearers attitude and motives to follow what speaker wants to. This research used qualitative approach. The data analyzed in this research are two speech of Trump about Jerusalem. The result showed that Trump used ethos, logos and pathos. Trump expressed pathos by showing his perceived intelligence, virtuous character and goodwill to create peace in Jerusalem. Logos were expressed while Trump showed factual information about the role of Israel in creating peace in Jerusalem. Trump mostly expressed pathos to affect hearers emotion by creating mildness, giving admiration and confession. Therefore, in achieving the goals of his speech, Trump intended to persuade hearers by touching their emotion.Key words: persuasive strategies, speech, Donald Trump